Perception and belief of dental concepts from toothpaste television advertisements of 10-11 year old children of Grace Park Elementary School - Canlas, Gladys Bloom P.
Advertisements are highly influential on children who regard them as sources of information. Toothpaste commercials contain dental concepts which can be grasped and thought to be true by children. The study aimed to identify the dental concepts perceived and believed by 10-11 year old children from two popular toothpaste advertisements. Specifically, the dental concepts contained in these particular commercials were evaluated for correctness. Those concepts perceived were identified and the subjects' belief on these were assessed. Questionnaires based on the commercials were formulated and used to survey 138 10-11 year old Grade five students of Grace Park Elementary School who were made to view the commercials. Findings revealed that dental concepts from toothpaste TV Ads whether correct or incorrect are perceived and believed by majority of 10-11 year old children. Furthermore, the Chi-Square Test for Independence showed that perception and belief of dental concepts have a significant relationship.